Incidence and predictors of chronic thromboembolic pulmonary hypertension following acute pulmonary embolism: An echocardiography guided approach - G. Agarwal (Elsevier, 2021)
There is significant variability in the worldwide epidemiology of chronic thromboembolic pulmonary hypertension (CTEPH). We thereby aim to determine the incidence and predictors of CTEPH, following an episode of acute pulmonary embolism (PE), using non-invasive modalities. Patients with acute PE were prospectively followed-up and after receiving at least 3 months of effective anticoagulation, persistently symptomatic patients with echocardiographic evidence of persistent pulmonary hypertension, were investigated further for CTEPH. Incidence of CTEPH was 8.19%. Delayed presentation, higher pulmonary artery pressures at presentation and discharge, and greater thrombotic burden were significant predictors for the development of CTEPH following acute PE.